PERUMUSAN STRATEGI PEMASARAN MENGGUNAKAN METODE QSPM PADA BISNIS SAMBAL NOESANTARA - Clara Amelinda Sugianto; Charly Hongdiyanto (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2017)
The company used to employ strategies to increase the sales of Sambal Noesantara; however, they failed to achieve such an objective. This study aims to determine the results of Maju Jaya Abadi company's strategy formulation using QSPM. This research used a descriptive qualitative method. For Business Development Strategy analysis, this study used EFE and IFE matrix, IE matrix, SWOT matrix and QSPM. The study found that Sambal Noesantara was in a strong position in making use of the power possessed and able to overcome the existing weaknesses the total IFE was 3.1459 whose value was classified as exploiting the existing opportunity level. Meabwgile, the value of EFE coping the threat was 2.7571. IE matrix showed that Sambal Noesantara has used growth and build strategies whose twelve alternative strategies can be used to develop its business